High intake of ultra-processed foods during the pandemic in people with anxiety and depression (Research, Society and Development, 2022)
Introduction: Given the current scenario of the COVID-19 pandemic, it is reasonable to expect that many behaviors will be modified, one of them being food. analyzing the high consumption of ultra-processed foods and the dietary factors that affect mental health. Objective: the objective is to investigate the interrelationship between the incidence of high consumption of ultra-processed foods during the COVID-19 pandemic and the influence of these foods on the body and mental health, highlighting people with anxiety and depression. Method: In the present study, a qualitative-quantitative study of literature review was carried out, covering books, magazines, Brazilian Society Guidelines, article bases on Pubmed, Academic (Scholar.Google), Scientific Electronic Library Online (Library Científica Eletrônica On-line) in the 2020s. Results: There is an intention to contribute with information on the subject with the aim of awakening a new vision and knowledge to the public in question, where it can contribute positively in the food field of people with anxiety and depression.